2023
DOI: 10.3390/molecules28124856
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloyl Glucose: A Review of Anticancer Properties, Molecular Targets, Mechanisms of Action, Pharmacokinetics, and Safety Profile

Abstract: Pentagalloyl glucose (PGG) is a natural hydrolyzable gallotannin abundant in various plants and herbs. It has a broad range of biological activities, specifically anticancer activities, and numerous molecular targets. Despite multiple studies available on the pharmacological action of PGG, the molecular mechanisms underlying the anticancer effects of PGG are unclear. Here, we have critically reviewed the natural sources of PGG, its anticancer properties, and underlying mechanisms of action. We found that multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…Therefore, these compounds might also contribute to the observed activity of DF. Probably, in the case of β-D-allopyranose, its effect could be the consequence of a different mechanism, such as oxidative stress, arrested cell proliferation, enhanced autophagy, apoptosis, or angiogenesis inhibition [108]. Similar behavior has been observed for other sugars such as glucopyranose or sugar polymers such as pectin [109].…”
Section: Gc-ms Analysismentioning
confidence: 71%
“…Therefore, these compounds might also contribute to the observed activity of DF. Probably, in the case of β-D-allopyranose, its effect could be the consequence of a different mechanism, such as oxidative stress, arrested cell proliferation, enhanced autophagy, apoptosis, or angiogenesis inhibition [108]. Similar behavior has been observed for other sugars such as glucopyranose or sugar polymers such as pectin [109].…”
Section: Gc-ms Analysismentioning
confidence: 71%
“…The researcher should thus consider their negative consequences at a high dosage. Recent research results showed that high doses of PGG (100 or 200 mg/kg/day) administered orally to mice did not have any adverse effects or cause weight loss in mice after seven days of therapy and that 200 mg/kg/day was the highest dose that could be tolerated; these results suggest that high doses of PGG are safe for mice [ 32 ]. PGG exhibits a propensity for lipids, polysaccharides, and proteins as evidenced by its slow clearance rate at 0.023 ± 0.012 h −1 and extended apparent elimination half-life (t 1/2 ) around 38.66 ± 22.89 h after intraperitoneal administration to rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallotannins, considered the simplest hydrolyzable tannins, are formed by gallic acid molecules bound to a central D-glucose with ester bonds (Figure 3) [82]. Tannic acid (penta-m-digalloyl glucose) is composed of a central glucose esterified to all five hydroxyl moieties with two molecules of gallic acid, totaling ten galloyl groups [83].…”
Section: Phenolic Compounds Of Quercus Sp Gallsmentioning
confidence: 99%